Balancing the Rights of Local Communities and the Creation of Protected Areas for the Conservation of Biodiversity Hotspots in Cameroon: Case Study of the Tofala Hill Wildlife Sanctuary (African Journal of Law and Politics, 2025)
Despite the significant contribution of protected areas in halting the degradation of natural resourcesand conserving biodiversity in Central Africa‚ the proliferation of this mechanism, is also beingquestioned by local communities who feel threatened with the dispossession of their lands bygovernments in complicity with conservators and non-governmental organizations (NGOs). Protectedareas have stirred up conflicts‚ with social and economic impacts that affect catchment communitieswho rely on forest resources found within these areas‚ who have seen their livelihood opportunitieseroded. This article closely examines the implications of creating protected areas on the rights of localcommunities in Cameroon‚ with a particular focus on the Tofala Hill Wildlife Sanctuary (THWS) inthe Wabane and Alou Sub-Division‚ in the South West Region of Cameroon. The article holds thatrather than promote communal land rights and participation in natural resource management‚ protectedareas for and conservation has strengthened state’s supremacy over local communities in themanagement of natural resource.